2021
DOI: 10.1039/d0cy02188a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable selectivity of phenol hydrogenation to cyclohexane or cyclohexanol by a solvent-driven effect over a bifunctional Pd/NaY catalyst

Abstract: Hydrogenation of phenol is an important strategy to produce cyclohexane or cyclohexanol as both of them are raw materials for the synthesis of nylon-6 and nylon-66.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Klyuev 35 found that the hydrogenation of nitrobenzene is a first-order reaction for catalyst and hydrogen, and a pseudo-zero-order reaction for nitrobenzene. So the significant influence of the solvent is assumed to be due to the sol pores changing the adsorption configuration of reducing groups on the transition metal surface 38 , Changed the potential energy field formed by the hydrogen bond between the original solvent and the organic matrix [39][40][41] . It can be concluded that the hydrogen bond with the metal is weaker to a certain extent, which is beneficial to the hydrogenation rate, and it is consistent with the phenomenon in the pressure screening process.…”
Section: Resultsmentioning
confidence: 99%
“…Klyuev 35 found that the hydrogenation of nitrobenzene is a first-order reaction for catalyst and hydrogen, and a pseudo-zero-order reaction for nitrobenzene. So the significant influence of the solvent is assumed to be due to the sol pores changing the adsorption configuration of reducing groups on the transition metal surface 38 , Changed the potential energy field formed by the hydrogen bond between the original solvent and the organic matrix [39][40][41] . It can be concluded that the hydrogen bond with the metal is weaker to a certain extent, which is beneficial to the hydrogenation rate, and it is consistent with the phenomenon in the pressure screening process.…”
Section: Resultsmentioning
confidence: 99%
“…6,16 As the hydrogen pressure increases, more H 2 can be dissolved in the solvent, thereby promoting the hydrogenation of phenol. 7,38 3.3.2 Influence of reaction temperature. Fig.…”
Section: 22mentioning
confidence: 99%
“…6 Cyclohexanol, as an indispensable synthetic intermediate for the production of hexamethylene diamine, caprolactam for nylon 6, and adipic acid for nylon 66, is an important commodity in the chemical industry. 7,8 It is a crucial raw material for the preparation of surfactants, detergents and plasticizers and has even greater industrial manufacturing prospects. 9,10 The production of cyclohexanol is mainly carried out through the oxidation of cyclohexane or the hydrogenation of phenol.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations